Job Evaluation in the New World of Work : How to Achieve Equal Pay for Work of Equal Value. - Bussin, Mark. (Knowledge Resources, 2022)
The new world of work has created unprecedented challenges for human resource practitioners. This book prompts exciting conversations on the question of: "What is the role of job evaluation". _x000D__x000D_With the developing concepts of blended work, work from anywhere and contingent workers, job evaluation systems will need some careful thought. One size and approach may not suit all situations and suggestions are offered on how to deal with these differing situations._x000D__x000D_The next domino after job evaluation is often remuneration, because pay scales are attached to the grades. Equal pay for work of equal value is probably one of the biggest focus points globally and clarity is offered in this book. The vertical pay gap and horizontal pay gap sometimes stem from the remuneration philosophy around pay scale design. This book clarifies how to do job evaluation in a changing world, how to develop pay scales and how to achieve equal pay for work of equal value._x000D_ _x000D_Contents include:_x000D_ _x000D_* What is Job Evaluation?_x000D_* Job Evaluation in the new world of work_x000D_* The Rise of the Contingent Workforce_x000D_* How to carry out the Paterson job evaluation_x000D_* The impact of job evaluation on salary structures_x000D_* Equal pay for work of equal value_x000D_* Measuring income inequality - a holistic approach_x000D_* The psychological impact of the new way of job evaluation.